Modeling of line impedance stabilization network impedance characteristic based on genetic algorithm. (July 2021) - Zhu, Zhibo; Zhao, Yang; Yan, Wei; Liu, Xingfa; Ju, Ming
Abstract: The line impedance stabilization network (LISN) is commonly used to measure the conducted electromagnetic interference (EMI) noise produced by electronic equipment. In order to improve the measurement accuracy of the conducted EMI noise, the characteristics of the LISN should be verified and calibrated, such as impedance and voltage division factor. However, the parasitic parameters of capacitance and inductance are critical to the performance of the LISN. In this paper, the high-frequency model of the LISN is proposed based on the topology and parasitic parameters. The impedance of the LISN is obtained from 150 ​kHz to 30 MHz based on scattering parameters method and vector network analyzer (VNA). The parasitic parameters of capacitance and inductance are extracted by employing the elite genetic algorithm (EGA), LISN topology and impedance. The voltage division factor and impedance of R&S LISN ENV216 is obtained and calculated by employing the proposed method, which verify the proposed method effectiveness. The work will contribute to the further design and calibration of the LISN, and improve the conducted EMI noise measurement accuracy.